The Essential Components of Metaverse-based Mixed Reality for Machinery Vocational Schools - Satrio Pradono Suryodiningrat; Harjanto Prabowo; Arief Ramadhan; Harry Budi Santoso (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2024)
Every nation is interested in the best practices of those with high enrolment in vocational schools and low young unemployment rates. We'd like to build robust systems that can deal with issues like the quick pace of technology development and the mismatch between supply and demand in the job market. Since Mark Zuckerberg rebranded the company as Meta in 2021, the Metaverse has seen a rise in popularity. The same can be said about mixed reality, which is currently in the spotlight following the release of Microsoft's first HoloLens. The authors propose a mixed reality as a means of resolving the problem of inadequately meeting the demand for skilled workers. The purpose of this study is to help machinery vocational schools decide whether or not to adopt a mixed reality as a teaching and learning tool by identifying the most important components of a metaverse-based mixed reality for such institutions and which metaverse type mixed reality belongs to. This study uses a methodology that is developed by the authors to accommodate the true or natural flow of this research. The results of this study are to provide the essential elements of mixed reality systems as the mixed reality systems are not part of any metaverse type. The implication of this study is since mixed reality is the combination of several metaverse types, the essential elements of mixed reality systems are taken from the components of the other metaverse types. The results of this study are to be a guide of what needs to be prepared before implementing a mixed reality system.